2022
DOI: 10.1210/jendso/bvac037
|View full text |Cite
|
Sign up to set email alerts
|

11-Oxyandrogens in Adolescents With Polycystic Ovary Syndrome

Abstract: Background/context Polycystic ovary syndrome (PCOS) is common and diagnosis requires an elevated testosterone. The clinical importance of adrenal 11-oxyandrogens in PCOS is unclear. We sought to determine if 11-oxyandrogens: 1) better identify PCOS diagnosis compared to testosterone 2) predict clinical comorbidities of PCOS, 3) are altered with combined oral contraceptive pill (COCP) or metformin therapy. Methods Data from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Early elevated 11KT may reflect the premature onset of adrenal gland maturation. The recent elucidation of conditions such as premature adrenarche and polycystic ovary syndrome manifesting with elevated 11KT ( 26 ), supports the notion of a mechanistic role for 11KT in premature adrenarche and conditions causing androgen excess. It is unclear if the increasing 11KT has a specific androgenic affinity for peripheral tissues such as bone and promotes skeletal maturation.…”
Section: Discussionmentioning
confidence: 78%
“…Early elevated 11KT may reflect the premature onset of adrenal gland maturation. The recent elucidation of conditions such as premature adrenarche and polycystic ovary syndrome manifesting with elevated 11KT ( 26 ), supports the notion of a mechanistic role for 11KT in premature adrenarche and conditions causing androgen excess. It is unclear if the increasing 11KT has a specific androgenic affinity for peripheral tissues such as bone and promotes skeletal maturation.…”
Section: Discussionmentioning
confidence: 78%
“…There was no difference in 11-KT levels obtained from the different sampling sites, again challenging the idea of a primarily ovarian 11-KT biosynthesis. While all published studies on PCOS and 11-oxygenated androgens ( 19 , 20 , 27 ) showed elevated levels of 11-OHA4 in comparison to controls, 11-KT seems only to be elevated in some ( 19 , 20 ), but not all women with PCOS ( 19 , 27 ). An elevation of 11-KT seems to be primarily found in women with PCOS who are obese but not in those who are only over- or normal-weighted ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 82%
“…It has been shown that 11-oxygenated androgens are elevated in adrenal-related androgen excess as congenital adrenal hyperplasia (CAH) or premature adrenarche and Cushing's disease [14,17,18]. In addition, they may also be elevated in some [19,20], but not all patients [21] with PCOS. However, as there is also in-vitro data claiming that there is a relevant production of 11-KT derived from the gonads [15], details of the biosynthesis of 11-oxygenated androgens in humans are debatable as direct evidence in terms of in-vivo data of localized secretion patterns is absent.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of hirsutism and acne was similar among the adolescents with PCOS diagnosed using Rotterdam or NIH criteria [ 68 ]. Lower mean mFG scores (6–8.5) were reported in cohorts of adolescents with PCOS in the USA including Hispanics and black adolescents [ 69 , 70 ]. Hirsutism defined as mFG score higher than 6 and higher than 8 was reported in 60–70% and 50% of adolescents with PCOS respectively [ 8 , 68 , 70 ].…”
Section: Main Criteria To Diagnose Pcos During Adolescencementioning
confidence: 99%
“…Hirsutism defined as mFG score higher than 6 and higher than 8 was reported in 60–70% and 50% of adolescents with PCOS respectively [ 8 , 68 , 70 ]. Higher hirsutism scores are related to higher testosterone levels according to population and cross-sectional studies of adolescents [ 59 , 60 , 69 , 71 , 72 ]. Hirsutism must also be distinguished from hypertrichosis, which is defined as excessive vellus hair distributed in a non-sexual pattern.…”
Section: Main Criteria To Diagnose Pcos During Adolescencementioning
confidence: 99%